ROTEM in the setting of liver transplant surgery reduces frozen plasma transfusion. (June 2021) - Al Moosawi, Muntadhar; Trudeau, Jacqueline; Smith, Tyler; Lefebvre, Alexandre; Shih, Andrew W.
Highlights: In our cohort of end-stage liver disease patients for transplantation, 95 % with INRs of 1.3–1.8 had normal ROTEM testing. Poor correlation between elevated INRs and ROTEM EXTEM clotting times was observed, improving only with INRs >3. With ROTEM use in our cohort, a significant reduction of plasma transfusion was observed, after adjusting for confounders. Our results suggest ROTEM may be advantageous for coagulation assessment in patients with liver disease compared to INR. Also, ROTEM may empower clinicians to resist the impulse to transfuse plasma for isolated elevated INRs. Abstract: Background: INR is traditionally used as a marker of clinical coagulopathy, but is suboptimal in liver disease patients due to rebalanced hemostasis and its ineffectiveness to predict bleeding. Rotational thromboelastometry (ROTEM) testing evaluates whole blood hemostasis, which may provide more accurate assessments with the EXTEM CT parameter than INR. Thus, in end-stage liver disease (ESLD) patients, we hypothesized that elevated INRs are associated with normal EXTEM CT values. Methods: A retrospective study assessing adult (>18) patients with ESLD and elevated INRs undergoing liver transplantation, was performed to assess correlations between INR and EXTEM CT. This included patients post-ROTEM implementation where all had pre-operative ROTEM testing; and patients up to one year pre-ROTEM implementation to compare transfusion utilization. Data abstracted also included patient demographics, coagulation testing results, liver disease etiology, and MELD score. Results: The study included 138 patients in the post-ROTEM group and 59 patients in the pre-ROTEM group. Normal EXTEM CT was observed in 95.3 % and 93 % of patients with INR of 1.3–1.8 and up to 3 respectively. There was no correlation between INR of 1.3–1.8 and EXTEM CT (⍴ = 0.239), and only moderate correlation was observed with higher INRs (⍴ = 0.617 with INRs >1.8). ROTEM-guided transfusion in liver transplant surgeries was associated with reduced plasma transfusion (OR 0.27, 95 % CI 0.12−0.58, p = 0.001) after adjusting for red cell utilization and coagulation testing. Conclusion: Our study suggests ROTEM may be advantageous for evaluating coagulopathy in patients with liver disease and ROTEM-guided transfusion reduces plasma transfusion.